Peranan Manajemen Sumber Daya Manusia Berbasis Nilai-Nilai Agama Pada Lembaga Pendidikan - Lelo, Elmagondulfa Habu (JURNAL PROPHETA, 2021)
Conceptually, human resource management in Indonesia is focused on understanding plan, implementing plan, and greater attention to managerialaspects and better utilization of people as organizational resources. In otherwords, human resource management is a reflection of the increasing significanceregarding the management of people in the organization as well as a broaderperspective on the assessment of this field. The urgency of human resource management such as first, humanresource management is not only ordinary strategic activities, but also issomething central in achieving organizational goals. Second, human resourcemanagers hand over responsibility for human asset management to senior linemanagement. Third, there is a shift from "industrial relations" to "employeerelations". The fourth creation and management of organizational culture is asimportant as the work of the organization itself, where individuals are given theopportunity to realize their full potential. Human resource management with itsconcept and vision can be used as a supporting and balancing factor in theincreasingly modern world of education that tends to be pursuing needs.